Intrecci di fiabe russe e tedesche in «Spaltkopf» di Julya Rabinowich: [Intertwinings of Russian and German fairy tales in Julya Rabinowich’s «Spaltkopf»] (Studia austriaca, 2020)
This article aims at providing an analysis as well as an interpretation of the novel Spaltkopf (2011) by the Russian-Austrian writer Julya Rabinowich, read through the lens of current theories on cultural transfer. Within this context it scrutinizes the references to Russian and German tales occurring throughout the novel. This analysis endeavours to establish how the osmotic synergy of the two cultural heritages, which are represented both through a new medium – the novel Spaltkopf – and via their original forms influenced by the visual-pictorial dimension, can be considered a valuable seismograph recording the processes of German-Russian cultural transfer.